قراءة سيميائية في غلاف المجموعة القصصية (المكحلة ) أحمد يوسف عقيلة - إلطيف تهاني عبد السلام محمد; قزيمة فاطمة الطيب (Al-Qurtas, 2025)
قراءة سيميائية في غلاف المجموعة القصصية (المكحلة ) أحمد يوسف عقيلة